2014
DOI: 10.1111/jace.13263
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemistry of Calcium Aluminosilicate Glasses

Abstract: The surface chemistry of synthetic calcium aluminosilicate glasses exposed to aqueous solutions of varying pH was described using zeta potential measurements and batch surface titrations. Element release and proton consumption were measured to characterize the reactions at the surface as a function of pH. It was found that proton-metal exchange or leaching was the dominant proton consumption process at low pH. The exchange reaction was observed to maintain charge balance, indicating that over the limited durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 47 publications
4
72
0
Order By: Relevance
“…Oka et al [36,37] reported an inhibitory effect of Ca, Zn and Al on corrosion rate of fused silica glass in 0.5 M and 1.5 M NaOH solutions, and attributed this to formation of a protective barrier layer. Snellings [10,34] studied dissolution of synthetic CaAl-Si glasses at 20°C and pH ≈ 13, and confirmed that Ca in the solution can significantly reduce the initial rate of glass corrosion. By studying borosilicate and nuclear glasses, Chave et al [31] reported that the passivating properties of PRI are enhanced when it contains calcium (originating either from the glass or the solution).…”
Section: Solid Products and The Role Of Calcium During Glass Dissolutionmentioning
confidence: 81%
See 1 more Smart Citation
“…Oka et al [36,37] reported an inhibitory effect of Ca, Zn and Al on corrosion rate of fused silica glass in 0.5 M and 1.5 M NaOH solutions, and attributed this to formation of a protective barrier layer. Snellings [10,34] studied dissolution of synthetic CaAl-Si glasses at 20°C and pH ≈ 13, and confirmed that Ca in the solution can significantly reduce the initial rate of glass corrosion. By studying borosilicate and nuclear glasses, Chave et al [31] reported that the passivating properties of PRI are enhanced when it contains calcium (originating either from the glass or the solution).…”
Section: Solid Products and The Role Of Calcium During Glass Dissolutionmentioning
confidence: 81%
“…(1) [9]. Leaching becomes significant at lower (acidic) pH, and increases the pH of the solution [9][10][11].…”
Section: Interactions Of Silicate Glass With Aqueous Solutionsmentioning
confidence: 97%
“…A significant reduction in dissolution speed above 90 μmol(Si)/L might indeed be associated with precipitation. Other factors behind the non-linear trends may include incongruent glass dissolution and protective layer formation, but these have been shown to be uncommon under alkaline conditions [15].…”
Section: Dissolution Experimentsmentioning
confidence: 99%
“…However, recent studies (Snellings, 2015;Snellings et al, 2014) evaluating the surface characteristics of synthetic glasses within the system Alkali-activated slag cements produced with a blended sodium carbonate/sodium silicate activator Bernal, San Nicolas, van Deventer and Provis Offprint provided courtesy of www.icevirtuallibrary.com Author copy for personal use, not for distribution CaO-Al 2 O 3 -MgO-SiO 2 demonstrated that these glasses dissolve congruently in alkaline media (pH above 11), independent of the content of magnesium oxide. The partial substitution of sodium carbonate by sodium silicate promoted a higher alkalinity (activator pH = 13·1) than is achievable in a sodium-carbonate-activating solution, and therefore congruent dissolution of the slag is more plausible in the system studied here.…”
Section: Nuclear Magnetic Resonance Spectroscopy the 29mentioning
confidence: 99%